2008
DOI: 10.1007/s00262-008-0568-4
|View full text |Cite
|
Sign up to set email alerts
|

Review of clinical studies on dendritic cell-based vaccination of patients with malignant melanoma: assessment of correlation between clinical response and vaccine parameters

Abstract: During the past years numerous clinical trials have been carried out to assess the ability of dendritic cell (DC) based immunotherapy to induce clinically relevant immune responses in patients with malignant diseases. A broad range of cancer types have been targeted including malignant melanoma which in the disseminated stage have a very poor prognosis and only limited treatment options with moderate effectiveness. Herein we describe the results of a focused search of recently published clinical studies on den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
141
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(151 citation statements)
references
References 73 publications
1
141
0
7
Order By: Relevance
“…Among the various cellular immune-monitoring methods, the ELISPOT assay is typically used to determine the frequency of effector cytokine (i.e., IFN-c)-secreting (CD8 1 ) T cells, and this assay has generated the most valuable results for evaluating the correlation between DC vaccine-induced immunological modulation and clinical response. 19 The value of the ELISPOT assay for measuring IFN-c-secreting T cells was also apparent in a previous study. 7 However, evidence for the importance of the tumor microenvironment and immune homeostasis in tumor development determined after measuring a single immunological parameter, such as cytotoxic T-cell activity, might not be sufficient to estimate the DC vaccine-induced anti-tumor response.…”
Section: Induction Of Ifn-c Secreting T Cellsmentioning
confidence: 95%
See 1 more Smart Citation
“…Among the various cellular immune-monitoring methods, the ELISPOT assay is typically used to determine the frequency of effector cytokine (i.e., IFN-c)-secreting (CD8 1 ) T cells, and this assay has generated the most valuable results for evaluating the correlation between DC vaccine-induced immunological modulation and clinical response. 19 The value of the ELISPOT assay for measuring IFN-c-secreting T cells was also apparent in a previous study. 7 However, evidence for the importance of the tumor microenvironment and immune homeostasis in tumor development determined after measuring a single immunological parameter, such as cytotoxic T-cell activity, might not be sufficient to estimate the DC vaccine-induced anti-tumor response.…”
Section: Induction Of Ifn-c Secreting T Cellsmentioning
confidence: 95%
“…25 The data obtained herein support a complicated role for CD4 1 CD25 high T-cell alterations in anti-tumor immunity, demonstrating a treatment-associated, but not clinically relevant, reduction. Previous studies have suggested 7,9,19 the significance of ELISPOT analysis for determining the relevance of immunemodulation in DC vaccine-associated clinical responses. The induction of IFN-c-secreting T cells was observed in seven of the 10 patients after DC vaccination, but with no clinical relevance ( Figure 5).…”
Section: Induction Of Ifn-c Secreting T Cellsmentioning
confidence: 99%
“…In a review by Engell -Noerregaard et al 4) , 57 of 626 malignant melanoma patients (9%) showed objective response (20 CR and 37 PR) when treated with DC -based vaccinations, but no significant correlations were noted between those objective response and the tested parameters. Many initial vaccine studies used DCs charged with one or few tumor antigens, whereas the potential of DCs rests with their still untapped capacity to elicit a strong and broad immune attack to lessen the chance of tumor escape.…”
Section: Discussionmentioning
confidence: 99%
“…, MASASHI KANAZAWA 1) , YU SATO 1) , ATSUSHI IRISAWA 2) , TADAYUKI TAKAGI 2) , TAKASHI OGATA 2) , SHOGO KASHIMURA 3) , AKIRA KENJO 3) , HIROYUKI SUZUKI 3) , MASAHIKO SHIBATA 4) , TATSUO SHIMURA 4) , HIROMASA OHIRA 2) , MITSUKAZU GOTO 3) , SEIICHI TAKENOSHITA 1) and HITOSHI OHTO…”
unclassified
“…By March 2010, almost 300 papers have been published reporting on 4422 patients treated (not all under Good Clinical Practice (GCP) conditions: primarily melanoma [32,33] and prostate cancer [34] patients -1301 and 510 patients, respectively). Most trials employed monocyte-derived DC (MoDC), which were most often generated from monocytes by culture in GM-CSF1IL-4 over approximately 6 days to obtain immature DC, followed by exposure to monocyte-conditioned medium or its mimic (cocktail composed of TNF-a1IL-1b1 IL-61PGE2) for 1-2 days, to yield ''cocktail''-matured DC.…”
Section: Adoptive Transfer Of Antigen-loaded DC Into Patients (Dc Vacmentioning
confidence: 99%